Asthma control test (ACT): comparison with the accurate use of inhalers for the treatment among patients with asthma - Jordy Oktobiannobel; Retno Ariza S. Soemarwoto; Fransisca Sinaga; Hetti Rusmini; Lutfi Indah Rahayu (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Asthma is a heterogeneous disease characterized by chronic inflammation of the respiratory tract. Pharmacological therapies that are often given by inhalation are Dry Powder Inhaler (DPI) and Metered-Dose Inhaler (MDI). According to the GLOBAL INITIATIVE FOR ASTHMA Asthma Control Test (ACT) is a questionnaire that can be used to measure the level of asthma controlPurpose: To determine the relationship between the correct use of inhalers and the results of the Asthma Control Test (ACT) in asthma patientsMethod: The design of this study was an analytic survey with a cross-sectional approach. The parameter used were asthma control test questionnaires taken from primary data in the form of a survey. There were 126 total samples of respondents who met the inclusion criteria, namely asthma patients who used inhalers and underwent at least 3 months of treatment.Results: Spearman correlation test was obtained p = 0.000 which means that there is a significant relationship between the accuracy of inhaler use and the results of the asthma control test and a strong positive correlation coefficient of r = 0.667 and, for the 95% confidence interval in this study, it was obtained (95%CI = 3.09-3.83).Conclusion: There is a relationship between the correct use of inhalers and the results of the asthma control test (ACT) in asthma patients.